Transgeneracijska transmisija "taboriščne izkušnje" in molk - Jurić-Pahor, Marija (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
TRANSGENERATIONAL TRANSMISSION OF "THE CONCENTRATION CAMP EXPERIENCE" AND SILENCE (WITH SPECIAL REGARD TO THE CASE OF SLOVENES IN CARINTHIA AND FRIULI VENEZIA GIULIA). The term "Transgenerational transmission" primarily refers to the empirical observation that parents (and grandparents) transmit their traumatic experience with their consequences to their children (and grandchildren). Special attention is given to the transmission of extreme traumatic experience of people, victims of persecution and confinement to concentration camps in the period of fashism and nazism. The author presents the topic in close relation to the phenomenon of silence, treating it as a complex and multi-meaning phenomenon, perceptible mostly on the subconscious level. This level which is related to the most subtle symbolical sphere (although it can also be a forceful form of communication) is studied with the help of scientific literature and (auto)biographically) conceived materials (written texts like testimonies, prose, poetry, film, art paintings, graphics), as well as narrative interviews (n=50), carried out within the basic reserch project, headed by the author herself and financed by the Public Agency for Research of the RS. The project as the article are above all focused on people, representing the so called first, second or third generations. These people mostly regard themselves as Slovenes, i.e. members of the Slovene national community in Carinthia and Friuli Venezia Giulia.
Keywords: Koroška; Friuli–Venezia Giulia; Furlanija-Julijska krajina; Primorska; Slovenian Littoral; narodne manjšine; zamejski Slovenci; nacizem; fašizem; koncentracijska taborišča